Safety and immunogenicity of BK-SE36/CpG malaria vaccine in healthy Burkinabe adults and children: a phase 1b randomised, controlled, double-blinded, age de-escalation trial - Ouédraogo, Alphonse; Bougouma, Edith Christiane; Palacpac, Nirianne Marie Q.; Houard, Sophie; Nebie, Issa; Sawadogo, Jean; Berges, Gloria D.; Soulama, Issiaka; Diarra, Amidou; Hien, Denise; Ouedraogo, Amidou Z.; Konaté, Amadou T.; et al. (Frontiers in Immunology, 2023)
Background BK-SE36/CpG is a recombinant blood-stage malaria vaccine candidate based on the N-terminal Plasmodium falciparum serine repeat antigen5 (SE36), adsorbed to aluminium hydroxide gel and reconstituted, prior to administration, with synthetic oligodeoxynucleotides bearing CpG motifs. In healthy Japanese adult males, BK-SE36/CpG was well tolerated. This study assessed its safety and immunogenicity in healthy malaria-exposed African adults and children. Methods A double-blind, randomised, controlled, age de-escalating clinical trial was conducted in an urban area of Ouagadougou, Burkina Faso. Healthy participants (n=135) aged 21-45 years (Cohort 1), 5-10 years (Cohort 2) and 12-24 months (Cohort 3) were randomised to receive three vaccine doses (Day 0, 28 and 112) of BK-SE36/CpG or rabies vaccine by intramuscular injection. Results One hundred thirty-four of 135 (99.2%) subjects received all three scheduled vaccine doses. Vaccinations were well tolerated with no related Grade 3 (severe) adverse events (AEs). Pain/limitation of limb movement, headache in adults and fever in younger children (all mild to moderate in intensity) were the most frequently observed local and systemic AEs. Eighty-three of BK-SE36/CpG (91%) recipients and 37 of control subjects (84%) had Grade 1/2 events within 28 days post vaccination. Events considered by the investigator to be vaccine related were experienced by 38% and 14% of subjects in BK-SE36/CpG and control arms, respectively. Throughout the trial, six Grade 3 events (in 4 subjects), not related to vaccination, were recorded in the BK-SE36/CpG arm: 5 events (in 3 subjects) within 28 days of vaccination. All serious adverse events (SAEs) (n=5) were due to severe malaria (52-226 days post vaccination) and not related to vaccination. In all cohorts, BK-SE36/CpG arm had higher antibody titres after Dose 3 than after Dose 2. Younger cohorts had stronger immune responses (12–24-month-old > 5-10 years-old > 21-45 years-old). Sera predominantly reacted to peptides that lie in intrinsically unstructured regions of SE36. In the control arm, there were no marked fold changes in antibody titres and participants’ sera reacted poorly to all peptides spanning SE36. Conclusion BK-SE36/CpG was well-tolerated and immunogenic. These results pave the way for further proof-of-concept studies to demonstrate vaccine efficacy. Clinical trial registration https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=1921, PACTR201701001921166.